Determinantes macroecológicos em padrões de arboviroses e seus vetores - Simon, Lorena Mendes (2020)
One of the greatest challenges faced by humanity is the emergence and spread of infectious diseases, which have harmed thousands of people throughout history. Although the transmission of pathogens is still a challenge for scientists and decision-makers, methodological tools are advancing in an attempt to predict its dynamics. Vector-borne diseases demonstrate a complex underlying structure that involves ecological processes and socioeconomic aspects. Although the temperature has been widely used to define geographical limits of transmission, our expectations indicate that considering it alone may not be a reliable alternative to predict the potential for disease transmission. Although the global climate is decisive for the fundamental niche of vectors and pathogens, the transmission of dengue is also driven by socioeconomic and microclimate aspects. The climatic suitability in subtropical and temperate areas indicates the possible advance of dengue transmission. Given the invasion of Aedes at high latitudes, the risk of introducing dengue in these regions depends on favorable microclimatic and socioeconomic aspects, although the expansion of these vectors towards the climate niche still available is a possibility.